Surface Form Accuracy Evaluation in Abrasive Lapping of Single-Crystal Silicon Wafers - Wang, Zhengwei; Lei, Yang; Wu, Xiaofeng (Frontiers in Materials, 2022)
Silicon-based materials still dominate the current semiconductor industry for the foreseeable years, such that it is needed in continuously developing the related advanced manufacturing technologies. For the abrasive precision lapping of single-crystal silicon wafer the surface form accuracy is very important which can significantly improve its efficiency and reduce the cost in the following ultra-precision polishing process. In this paper, a novel driving system is proposed in the single-side planetary lapping process that could realize the irrational rotation speed ratio of the lapping plate to workpiece, and it is found from numerical qualitative and quantitative analysis that the uniformity of the particle trajectories moving on the target surface has been significantly improved by using the irrational rotation speed ratio, and hence resulting in the higher surface form accuracy than that driven by the rational rotation speed ratio. Moreover, an in-house developed irrational rotation speed ratio driving system has been made for the experimental study, and it is found that the effect of the rational and irrational rotation speed ratios on the surface roughness is not significant while all the five essential values related to the surface form accuracy are better under the rotation speed ratio of i=1.0772… than that under the rotation speed ratio of i=1, which demonstrates that the irrational rotation speed ratio driving system has the advantage of being able to obtain a good surface form accuracy and agrees well with the numerical simulation results.